Structural Behavior of BubbleDeck Slab under Uniformly Distributed Load - Ali Sabah Mahdi; Shatha Dehyaa Mohammed (Salehan Institute of Higher Education, 2021)
In structural construction fields, reducing the overall self-weight of the structure is considered a primary objective and substantial challenge in the civil engineering field, particularly in earthquake-affected buildings and tall buildings. Different techniques were implemented to attain this goal; one of them is setting voids in a specific position through the structure, just like a voided slab or BubbleDeck slab. The main objective of this research is to study the structural behavior of BubbleDeck reinforced concrete slabs under the effect of static uniformly distributed load. The experimental program involved testing five fixed-end supported two-way solid and BubbleDeck slabs of dimensions 2500×2500×200 mm. The considered parameters included the bubble's diameter 100 and 120 mm and the concrete volume reduction 15 and 18 %. The other parameters, which are concrete compressive strength and detail of the steel reinforcement, were identical for all the tested specimens to be for the compressive strength and (∅ 10 @164 mm) for the steel reinforcement. The outcomes indicated that the ultimate load capacity for a BubbleDeck slab decreased by 15.93 and 11.5 % compared to the solid slab in case of concrete volume reductions 18 and 15 %, respectively. On the other hand, an advanced behavior, including the ultimate deflection, the absorbed energy, and the ductility factor, was achieved; the increments in these parameters were 39, 5.3, and 14.94 %, respectively. Doi: 10.28991/cej-2021-03091655 Full Text: PDF